Exosomes derived from stem cells from the apical papilla alleviate inflammation in rat pulpitis by upregulating regulatory T cells. (29th March 2022) - Yu, Si; Chen, Xu; Liu, Yao; Zhuang, Xue Y.; Wang, Ao C.; Liu, Xue M.; Zhu, Shu
Abstract: Aim: To evaluate the effects of exosomes derived from stem cells from the apical papilla (SCAP‐Exos) in rats with experimentally induced pulpitis and the effects of SCAP‐Exos on the conversion of regulatory T cells (Tregs) and methylation status of the Foxp3 locus in Tregs in vitro . Methodology: SCAP‐Exos were isolated and identified using transmission electron microscopy, western blotting, and nanoparticle tracking analysis. Lipopolysaccharide was used to experimentally induced pulpitis in rats, and the effects of SCAP‐Exos on the rats with pulpitis were detected using haematoxylin‐eosin staining and immunofluorescence staining. CD4 + CD25 ‐ T cells were treated with different doses of SCAP‐Exos, and flow cytometric analysis was used to assess the effects of SCAP‐Exos on Treg proliferation and conversion. An enzyme‐linked immunosorbent assay (ELISA) was used to evaluate the expression of interleukin 10 (IL‐10). MethylTarget ® technology was used to measure the methylation level of the Foxp3 locus in T cells. The expression levels of ten‐eleven‐translocation (Tet) 1, Tet2, and Tet3 in T cells were detected by real‐time PCR and western blotting. Results: SCAP‐Exos had an elliptical vesicle‐like structure with a diameter of approximately 143.7 nm and expressed the exosomal markers Alix and CD9. SCAP‐Exo administration increased Treg accumulation in the inflamed dental pulp and alleviated inflammation in the dental pulp in vivo . SCAP‐Exos promoted Treg conversion in vitro . Mechanistically, SCAP‐Exos promoted Tet2‐mediated Foxp3 demethylation to maintain the stable expression of Foxp3. Conclusions: SCAP‐Exos promoted Treg conversion and effectively alleviated inflammation in the dental pulp of rats. This study shows that SCAP‐Exos can regulate the local immune microenvironment to favour tissue regeneration, thus providing a potential novel strategy utilising SCAP‐Exos as a cell‐free approach to treat early inflammation of dental pulp in immature permanent teeth in the clinic. Abstract : SCAP‐Exos promoted Treg conversion to alleviate inflammation in the dental pulp of rats. Mechanistically, SCAP‐Exos improved the positive expression of Foxp3, further stabilized the expression of Foxp3 through Tet2‐mediated Foxp3 demethylation for Treg conversion.